Language Proficiency and Partial Immersion Program at Vocational of Education Technology - Nuraeni Kasman; Muhammad Hanafy; Andi Sadapotto; Besse Tuti Alawiah (Edumaspul: Jurnal Pendidikan, 2021)
The goal of this article decide any improvement in the mastery of student language proficiency in terms of discuss class after being taught by partial immersion program at Vocational Education Technology.With the use of experimental method this research design is quantitative. On June 2020, this research was conducted in two weeks. On June 2020, this research was conducted in two weeks. The subject of this article was education technology students college consisting of 12 students in the second semester. Methode of collection data was test of pre-test and post-test. Data analysis techniques were calculating Heaton 's speaking test interview by disscussion class software and the spss statistical method.The result show that: Posttest is bigger than Pretest's. For Pretest Acquired, score means 51.80. In Posttest grew to 55.00. Certainly there is an improvement in students ' language proficiency through partial immersion program so that the dominant theory hypothesis is H1 (Alternative Hypothesis).It can be concluded that partial immersion program can improve the language proficiency students college.